Real Time-PCR (RT-PCR) Positivity for SARS-CoV-2 in Suspected COVID-19 Patients Presented in a Tertiary Care Hospital - Biswas, Sarmistha; Azad, Khan Abul Kalam; Hoque, Mohammad Mahfuzul; Mowla, Syed Ghulam Mogni; Banu, Sultana Shahana; Sharmin, Rabeya; Shamsuzzaman, SM (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Introduction: Corona Virus Disease 2019 (COVID-19) is caused by SARS-CoV-2, a newly emergent virus. World Health Organization declared COVID-19 as pandemic on March 11, 2020 for its rapid spreading. Not only to diagnose the disease (confirm case) but also to control and contain the transmission; test, trace and isolation are fundamental. RT-PCR for SARS-CoV-2 is used to detect and diagnose COVID-19 which started in Dhaka Medical College Hospital (DMCH) on 2nd April 2020. In this study we described our observation of RT-PCR done in patients presented in DMCH in the first month after starting the test. Methods: This observational, cross sectional study was done to find out the rate of RT-PCR positivity in suspected COVID -19 patients presented to DMCH from 2nd April to 3rd May, 2020 by the Department of Medicine in association with the Department of Virology. Data was collected from the registry book of the Department of Virology. The rate of RT-PCR for SARS-CoV-2 positivity among the suspected COVID-19 patients and demographical variable was observed. Results: Among the total studied patients (n=3206), 58.8% (n=1886) was male and mean age was 37.7(±14.38784) years. RT-PCR for SARS- CoV-2 was positive in 26.9% (n=864). Mean age was higher in patients positive for test (39.6± 15.9 year vs. 37±14.4 year). Male predominance was more marked in patients with positive PCR test (68.4 vs. 55.9). Conclusion: High rate of positivity of RT PCR for SARSCoV- 2 among the suspected patient for COVID 19 indicated high disease burden and transmission in this highly populated area in the early period of pandemic which should be considered as was alarming. J Bangladesh Coll Phys Surg 2020; 38(0): 67-70